The Influence of Transformational Leadership, Work Discipline, and Work Motivation on Employees' Work Goals: Pengaruh Kepemimpinan Transformasional, Disiplin Kerja, dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Alamsah, Dandi; Prapanca, Detak (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine and analyze whether the Effect of Transformasional Leadership on employee Job Satisfaction, to find out and analyze whether Work Discipline has an effect on Employee Job Satisfaction, to determine and analyze whether Work Motivation has an effect on Employee Job Satisfaction. This study used a sample of 42 respondents. This research method uses quantitative. The technique of determining the informants used purposive sampling techique. The result of the t test (partial) show thaht the variables of Transformational Leadership, Work Discipline, and Work Motivation have a significant effect on Job Satisfaction. Employee Work at PT Sarana Nikoteknik Surabaya the result of the coefficient of determination test is known that the value of r square is 0,463, this shows that the contribution of Transformational Leadership (X1), Work Discipline (X2), and Work Motivation (X3) on Employee Job Satisfaction (Y) is by 46,3% while the remaining 53,7% is explained by other variables not examined in this study.